Impacts of the Tourism Environment on Economic Activities at Wat Phra That Phanom, Thailand - NONTHAPOT, Sakkarin; WONGSIRI, Aphiradee (Journal of Environmental Management and Tourism, 2019)
This study aims to investigate the influence of physical and social factors in the tourism environment that affect the economic activities of Wat Phra That Phanom, Nakhon Phanom Province. The economic activities comprise production, consumption, distribution, and exchange. The samples were collected from 250 Thai tourist respondents. The research instrument employed was a questionnaire using convenience sampling. The analysis employed the Ordinary Least Square (OLS) method. The results show that the environmental factor in regard to physical tourism had a positive effect the economic activities involving production and distribution. Ecological factors in regard to social tourism influenced economic activities involving consumption and distribution. From the research results, Wat Phra That Phanom should manage its physical environment by designing layouts that appeal to Thai and foreign tourists. In regard to environmental management, staffs should pay more attention to safety at Wat Phra That Phanom